The battle of Newton Road - Dunkling, Leslie, 1935- (Harlow : Pearson Education, 2008)
"The houses in Newton Road are small, but people are very happy there. Then a civil engineer wants to knock down the houses and build a new road. The people of Newton Road are very angry. But can they win the battle?"--Page 4 of cover
"The houses in Newton Road are small, but people are very happy there. Then a civil engineer wants to knock down the houses and build a new road. The people of Newton Road are very angry. But can they win the battle?"--Page 4 of cover
Keywords: Urban renewal -- Fiction; Roads -- Design and construction -- Fiction; Protest movements -- Fiction; Readers